2012
DOI: 10.1371/journal.pone.0035122
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Chemical Activation of Nrf2

Abstract: NF-E2 related factor-2 (Nrf2) promotes the transcription of many cytoprotective genes and is a major drug target for prevention of cancer and other diseases. Indeed, the cancer-preventive activities of several well-known chemical agents were shown to depend on Nrf2 activation. It is well known that chemopreventive Nrf2 activators stabilize Nrf2 by blocking its ubiquitination, but previous studies have indicated that this process occurs exclusively in the cytoplasm. Kelch-like ECH-associated protein 1 (Keap1) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 42 publications
5
104
0
Order By: Relevance
“…Consistent with these observations, several reports have shown that modification of Cys-151 inhibits the Keap1-Cul3 interface and prevents ubiquitination of Nrf2 (30,41). It should be noted that there are a couple of reports that disagree with this model (46,47). For instance, the Keap1-Cul3 complex does not dissociate upon exposure to 5,6-dihydrocyclopenta-1,2-dithiole-3-thione or sulforaphane (46).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with these observations, several reports have shown that modification of Cys-151 inhibits the Keap1-Cul3 interface and prevents ubiquitination of Nrf2 (30,41). It should be noted that there are a couple of reports that disagree with this model (46,47). For instance, the Keap1-Cul3 complex does not dissociate upon exposure to 5,6-dihydrocyclopenta-1,2-dithiole-3-thione or sulforaphane (46).…”
mentioning
confidence: 73%
“…It should be noted that there are a couple of reports that disagree with this model (46,47). For instance, the Keap1-Cul3 complex does not dissociate upon exposure to 5,6-dihydrocyclopenta-1,2-dithiole-3-thione or sulforaphane (46). Similarly, a live-cell imaging analysis showed no dissociation of the Keap1-Cul3 complex upon exposure to 1-[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl] (CDDO), sulforaphane, sulfoxythiocarbamate alkyne, or hydrogen peroxide (47).…”
Section: Minireview: Stress Response By the Keap1-nrf2 Systemmentioning
confidence: 95%
“…29,30 We found that after incubation with resveratrol for 6 hours, NRF2 dissociated from Kelch-like ECH-associated protein 1 and translocated to the nucleus, where it became active ( Figure 4A). This was associated with overexpression of MnSOD ( Figure 3D).…”
Section: Resveratrol Activates Mnsod Through Nrf2mentioning
confidence: 98%
“…In humans, enhanced Nrf2 expression is found in various types of epithelial cancer bearing mutations within the NRF2 gene (18) and also in oncogene-driven cancer tissue, where Nrf2 promotes antioxidant programs (19). SFN directly activates Nrf2 by binding cysteine residues of kelch-like ECH-associated protein 1 (Keap1), which is responsible for Nrf2 ubiquitination (20). SFN blocks the function of Keap1, resulting in Nrf2 stabilization.…”
mentioning
confidence: 99%